Implementation of diffusion model in realistic face generation - Rahman, Abidur; Al-Mamoon, Faiyaz; Saquib, Mohammad Nazmus; Bahar, Farhan Bin; Fabia, Mukarrama Tun (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.